Neonatal exposure to the experimental environment or ketamine can induce long-term learning dysfunction or overmyelination in female but not male rats. Issue 7 (1st May 2019) - Zhang, Junfang; Chen, Bo; Deng, Xiaoyuan; Wang, Bin; Liu, Hongliang
Abstract : Ketamine can induce neurotoxicity after exposures to the developing brain. To investigate whether ketamine at subanesthetic dosage or its environmental condition can cause long-term cognitive dysfunction after multiple exposures in male or female neonatal rats, postnatal day 5 (P5)-day-old Sprague-Dawley rats were randomized into three groups: ketamine group, vehicle group, and control group (no disturbance). Learning and memory abilities from P60 to P65 and immunofluorescence tests for myelin basic protein (MBP) in gray matter on P65 were conducted. The results showed that in female rats, the path length on day 1 in ketamine group and on days 1 and 2 in vehicle group was longer than that in control ( P <0.05), but there was no difference between ketamine and vehicle groups ( P >0.05). The mean density of MBP in the medial prefrontal cortex (mPFC) was significantly increased in vehicle and ketamine groups compared with that in control ( P <0.05), and there was a significant difference between vehicle and ketamine groups ( P <0.05), but MBP density was not changed in CA1 or CA3 region ( P >0.05). In male rats, there were no significant differences in path length among the groups, and the density of MBP in the mPFC and hippocampus in vehicle or ketamine group was not different from that in control ( P >0.05). Pearson's correlation analysis showed that there was a positive correlation between MBP density in the mPFC and path length in adult female rats ( r =0.753, P <0.01). Overall, the results suggested that neonatal female rats exposed to multiple episodes of the experimental environment can develop learning dysfunction in adulthood, which may result from overmyelination in the mPFC, but male rats were not affected. Ketamine could increase myelination in the mPFC in female rats, but it did not induce learning dysfunction in adulthood; therefore, ketamine may be a safe drug for pediatric anesthesia.